Management of sexual health issues in adolescents and young adults with congenital lower urinary tract malformations: concerns emerging from a survey of Italian pediatric urology centers - Rachele Borgogni; Claudia Gatti; Francesca Caravaggi; Ilaria Manghi; Alfredo Berrettini; Dario Guido Minoli; Maria Luisa Capitanucci; Ermelinda Mele; Paolo Caione; Giuseppe Cretì; Evi Comploj; Marcello Carlucci; et al. (Frontiers in Pediatrics, 2026)
Introduction Transitional care of patients with complex uro-genital malformations (CUGM), including spina bifida, bladder exstrophy-epispadias complex, cloaca, congenital adrenal hyperplasia, and vaginal atresia, remains a worldwide challenge. These conditions are associated with lower urinary tract dysfunction (LUTD), long-term urinary morbidity, and significant psychosocial consequences. The aim of this study was to investigate how pediatric urologists in Italy address sexuality and fertility in adolescents and young adults with CUGM. Materials and methods A 23-item multiple-choice-questionnaire was developed by the Italian Society of Pediatric Urology (SIUP) to investigate health care current provider practices regarding sexual health, fertility, gender identity, and transitional care in adolescents and adults with congenital urogenital malformations (CUGM). Each participating center completed one questionnaire after reviewing its actively followed patient cohort. Data were analyzed at the center level using descriptive statistics. Results With a 95% response rate, data from 725 patients were collected. Most centers (43%) followed 20–50 patients; 12.5% managed 50–100, and only two followed >100. Multidisciplinary teams were present in 75% of centers, including psychologists (62.5%) and sexologists (25%). All responding centers reported to have in follow-up sexually active patients; 7% of centers reported caring for patients with history of sexual abuse. Sexual health topics were routinely addressed: erectile dysfunction (93%), ejaculation (87.5%), vaginal lubrication (81%), contraception (62.5%), STDs (75%), and pregnancy (75%). Validated questionnaires were applied only in 19% of centers in males and 7% in females. Sexual issues were discussed in the presence of relatives in 31% of centers. 69% of centers reported addressing or identifying substance abuse among their patients. Pelvic organ prolapse screening was performed in 19%. 56% of centers reported following patients identifying as homosexual or bisexual, while transgender identity was reported in 12.5%. Although 69% of centers felt confident discussing gender dysphoria, only 31% were familiar with the GIDYQ-AA; all healthcare professionals expressed the need for additional training on gender identity. Conclusion This national provider survey highlights important gaps in the organization of transitional sexual healthcare for patients with CUGM. The findings reflect current practices among Italian pediatric urology centers and support the development of standardized multidisciplinary transition pathways.